Fanconi anaemia complementation group B presenting as X linked VACTERL with hydrocephalus syndrome. Issue 9 (5th May 2006) - Holden, S T; Cox, J J; Kesterton, I; Thomas, N S; Carr, C; Woods, C G
Abstract : Background: The VACTERL with hydrocephalus (VACTERL-H) phenotype is recognised to be a severe manifestation of autosomal recessive Fanconi anaemia. Several families have been described in which the VACTERL-H phenotype segregates as an X linked syndrome. The mutations which cause X linked VACTERL-H syndrome are not known. Objective: To determine if mutations in FANCB, which are known to cause Fanconi anaemia complementation group B, are a cause of X linked VACTERL-H syndrome. Methods: A three generation pedigree with X linked VACTERL-H syndrome was investigated. X inactivation was tested in carrier females, and fibroblasts from an affected male fetus were analysed for increased sensitivity to diepoxybutane. FANCB coding exons and flanking splice sites were screened for mutations by direct sequencing of polymerase chain reaction (PCR) fragments amplified from genomic DNA. cDNA from affected fetal fibroblasts was analysed by PCR and direct sequencing using specific exonic primers. Results: A FANCB mutation which results in a premature stop codon by causing skipping of exon 7 was identified. Chromosomes from the affected fetus showed increased sensitivity to diepoxybutane, and carrier women were found to have 100% skewed X inactivation in blood. Conclusions: Mutations in FANCB are a cause of X linked VACTERL-H syndrome. The data presented are of relevance to the genetic counselling of families with isolated male cases of VACTERL-H and Fanconi anaemia.